PERLINDUNGAN HUKUM LENDER DALAM TRANSAKSI PEER TO PEER LENDING KAITANNYA PLATFORM YANG MELAKUKAN PERBUATAN MELAWAN HUKUM - Nabila Rahma Gustami; Yudho Taruno Muryanto (Jurnal Privat Law, 2023)
This article aims to find out the first, the regulation of peer to peer lending transactions in the rule of law in Indonesia and the second, the form of legal protection against lenders in peer to peer lending transactions in relation to platforms that commit illegal acts. This type of research is normative with a prescriptive nature of research. Based on the results of research and discussion, the authors show that the regulation of peer to peer lending transactions in the rule of law in Indonesia has been regulated in several regulations, Undang-Undang Number 21 of 2011, Undang-Undang Number 11 of 2008 as amended by Undang-Undang Number 19 of 2016 , Financial Services Authority Regulation Number 77 / POJK.01 / 2016, Financial Services Authority Regulation Number 13 / POJK.02 / 2018, Bank Indonesia Regulation Number 19/12/ PBI / 2017. And as for the form of legal protection for lenders in peer to peer lending transactions, the relationship between platforms committing acts against the law is regulated in the Financial Services Authority Regulation Number 77/POJK.01/2016